ANALISIS PERSEPSI PEKERJA: PERANAN SALARY, COMPETITION, DAN ENJOYMENT TERHADAP JOB PRODUCTIVITY - Syarifah Mauli Masyithah; Zenitha Maulida; Teuku Muhammad Jumeil; Teuku Muhammad Syauqi (Universitas Dharmawangsa, 2023)
The study's goal is to investigate the impact of salary, competition, and job enjoyment on workers' perceptions of job productivity. The sample size of this study is 21 workers from PT Era Permata Sejahtera Banda Aceh. The results of the partial testing of salary variables have a significant positive impact on job productivity. The competition has an influence on the job productivity of the employees. Partially, salary and competition have a significant positive impact on job productivity, but not on job enjoyment. Simultaneously, salary, competition, and job enjoyment have a significant influence on the employee's productivity.Keywords: salary, competition, job enjoyment, job productivity